Designer hydrogels: Shedding light on the physical chemistry of the pancreatic cancer microenvironment. (1st November 2018) - Lin, Chien-Chi; Korc, Murray
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is currently the third leading cause of cancer mortality in the United States, with a 5-year survival of ∼8%. PDAC is characterized by a dense and hypo-vascularized stroma consisting of proliferating cancer cells, cancer-associated fibroblasts, macrophages and immune cells, as well as excess matrices including collagens, fibronectin, and hyaluronic acid. In addition, PDAC has increased interstitial pressures and a hypoxic/acidic tumor microenvironment (TME) that impedes drug delivery and blocks cancer-directed immune mechanisms. In spite of increasing options in targeted therapy, PDAC has mostly remained treatment recalcitrant. Owing to its critical roles on governing PDAC progression and treatment outcome, TME and its interplay with the cancer cells are increasingly studied. In particular, three-dimensional (3D) hydrogels derived from or inspired by components in the TME are progressively developed. When properly designed, these hydrogels (e.g., Matrigel, collagen gel, hyaluronic acid-based, and semi-synthetic hydrogels) can provide pathophysiologically relevant compositions, conditions, and contexts for supporting PDAC cell fate processes. This review summarizes recent efforts in using 3D hydrogels for fundamental studies on cell-matrix or cell-cell interactions in PDAC. Highlights: Tumor microenvironment (TME) governs progression and treatment outcome of pancreatic ductal adenocarcinoma (PDAC). 3D hydrogels derived from or inspired by components in the TME are progressively used to recapitulate PDAC tumor matrix. Cell-laden hydrogels can provide relevant compositions, conditions, and contexts for supporting PDAC cell fate processes. This review summarizes recent efforts in using hydrogels for studying cell-matrix or cell-cell interactions in PDAC.